Pengaruh Konsumsi Fast Food terhadap Obesitas pada Remaja - Vera Vera (Lembaga Pengembangan Kinerja Dosen, 2025)
Adolescent obesity is an increasingly global public health concern, including in Indonesia. Fast food consumption characterized by high calories, fat, sugar, and sodium with low essential nutrients has been identified as a major contributing factor. This study aimed to analyze the association between fast food consumption and obesity in adolescents and evaluate other influencing factors such as socioeconomic status, physical activity, and psychological aspects. This descriptive analytical literature review used secondary data sourced from journals, books, and research reports, obtained through PubMed, Google Scholar, and ScienceDirect, with strict inclusion and exclusion criteria. Findings indicate a significant relationship between fast food consumption and increased obesity risk among adolescents. Socio-cultural influences, including advertising and accessibility, also shape dietary habits. Implications suggest the need for stricter fast food advertising regulations, improved nutrition education, and policies limiting fast food availability around adolescents. Routine fast food consumption has been proven to elevate obesity risk, underscoring the urgency of promoting healthy lifestyles and reducing fast food accessibility as preventive strategies.